Anthropology “at no cost” but Anthropology nontheless. Presentation of the monographic issue: Anthropology, Globalization and Ethnographic Practices - Córdoba Azcárate, Matilde; Córdoba Azcárate, Matilde (Revista de Antropología Social, 2012)
This paper is the introduction to the monographic issue Anthropology, globalization and ethnographic practices. It is organized in two main sections which explore the context, objectives and orientation of the special number, as well as each contribution in detail. Using a wide and open definition of globalization, the contributions to this issue can be organized in two main sections: the ones that pay special attention to the vectors and socio-spatial impacts of globalization as an economic, political and technological process; and those papers which urge to articulate alternatives to hegemonic globalization and that do so by using an anthropological knowledge and practice.